Aplicación de la sección 23 y 11 instrumentos financieros para recuperar las cuentas por cobrar en Emeloy Servicios Educacionales C. Ltda. - Matamoros Ochoa, María Fernanda (Machala : Universidad Técnica de Machala, 2022)
The investigative work addresses an analysis of the International Financial Reporting Standards for small and medium-sized companies, specifically of financial instruments and operating income, which has an important impact on the structure of financial statements because there are many companies that They apply credit policies in their sales and in turn clearly differentiate their income between operating and non-operating, hence the significance of the study that is used for similar companies within the business environment. The object of study is the company Emeloy Servicios Educacionales C. Ltda., Applying a questionnaire as an instrument for collecting information, the same that served to know the reality of the processing of accounting information of accounts receivable and their sales, counteracting it with the provisions of international accounting regulations; At the end, the main conclusions are left, among which stand out that the company should recognize and value the financial instruments and operating income in relation to what the generally accepted accounting principles have in order for the economic information to be reliable, comparable , reliable and understandable.
El trabajo investigativo aborda un análisis de las Normas Internacionales de Información Financiera para la pequeñas y medianas empresas, específicamente de los instrumentos financieros y los ingresos operacionales que tiene una incidencia importante dentro de la estructura de los estados financieros, debido a que son muchas las empresas que aplican en sus ventas políticas de crédito y a su vez diferencian de forma clara sus ingresos entre operativos y no operativos, de ahí la significancia del estudio que sirve para empresas similares dentro del entorno empresarial. El objeto de estudio es la empresa Emeloy Servicios Educacionales C. Ltda., aplicando un cuestionario como instrumento de recolección de la información, la misma que sirvió para conocer la realidad del procesamiento de la información contable de las cuentas por cobrar y sus ventas, contrarrestándola con las disposiciones de la normativa contable internacional; al finalizar se dejan las principales conclusiones entre las que se destacan que la emrating income in relation to what the generally accepted accounting principles have in order for the economic information to be reliable, comparable , reliable and understandable. que la información económica sea confiable, comparable, fiable y comprensible
Keywords: INSTRUMENTOS FINANCIEROS; INGRESOS OPERATIVOS, INGRESOS OPERACIONALES; NORMATIVA CONTABLE